2012
DOI: 10.3892/ijo.2012.1707
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 regulates biological behavior through the PTEN/PI-3 K/Akt signaling pathway in human colorectal cancer cells

Abstract: The aim of this study was to determine a role of microRNA-21 (miR-21) in colorectal cancer (CRC) and to elucidate the regulation of phosphatase and tensin homologue (PTEN) gene by miR-21. MiR-21 expression was investigated in 30 CRC samples and five CRC cell lines. In this study, we show that the expression of miR-21 was overexpressed in CRC compared with adenomas and normal tissues. Patients with poor differentiation, lymph node metastasis and advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 65 publications
10
113
1
1
Order By: Relevance
“…Moreover, Sheng et al [26] found that the protein kinase/phosphatase/phosphatidyl-inositol kinase (AKT/PTEN/ PI3K) signaling pathway is intimately linked with many malignant tumors and their progression, drug resistance, immunity, angiogenesis, and metastasis [27,28]. Furthermore, there have been several studies showing that miR-21 has a significant role in regulating the AKT/ PTEN/ PI3K signaling pathway and contributes to the initiation of carcinogenesis, tumor progression, and metastasis [29,30]. Sheng et al [26] reported that the PTEN gene is a direct target gene of miR-21.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sheng et al [26] found that the protein kinase/phosphatase/phosphatidyl-inositol kinase (AKT/PTEN/ PI3K) signaling pathway is intimately linked with many malignant tumors and their progression, drug resistance, immunity, angiogenesis, and metastasis [27,28]. Furthermore, there have been several studies showing that miR-21 has a significant role in regulating the AKT/ PTEN/ PI3K signaling pathway and contributes to the initiation of carcinogenesis, tumor progression, and metastasis [29,30]. Sheng et al [26] reported that the PTEN gene is a direct target gene of miR-21.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of studies, including our study, indicate that in most solid tumors, miR-21 promotes the proliferation and metastasis of tumor cells by targeted inhibition of PTEN, a few investigators have reported conflicting results (Xiong et al 2013). Hatley et al (2010) reported that PTEN is not a target gene of miR-21 in NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…PTEN also has been confirmed as a target gene of miR-21 in nonsmall cell lung cancer (Zhang et al 2010), gastric cancer (Zhang et al 2012), cervical cancer (Xu et al 2015), and colorectal cancer (Xiong et al 2013). Deletions or inactivated mutations of PTEN can mediate the promotional effect of miR-21 on the proliferation, invasion and metastasis of tumor cells (Selcuklu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we observed that pretreatment with paeonol also reversed the suppression of PTEN expression induced by ox-LDL. Interestingly, studies have demonstrated that PTEN is a downstream target gene of miR-21 in cancers [16][17][18][19] , because its 3'-UTR contains 16 base sites that are complementary to the miR-21 sequence [1,20] . However, it is unknown whether paeonol-mediated protection of VECS against ox-LDL injury involves miR-21-dependent modulation of PTEN.…”
Section: Discussionmentioning
confidence: 99%